The Avengers : These are the Avengers - Macri, Thomas; Norton, Mike.; Hi-Fi Colour Design; Marvel Comics Group (New York : Marvel Press, 2012)
Describes the powers and abilities of the members of the Avengers, including Ant-Man, Hulk, and Thor.
"Based on the Marvel comic book series "The Mighty Avengers."
"Marvel."
Illustrated by Mike Norton and Hi-Fi Design.
Accelerated Reader
Keywords: Avengers (Fictitious characters) -- Juvenile fiction; Superheroes -- Juvenile fiction; Avengers (Fictitious characters); Superheroes; Fiction; Juvenile works